Analysis of The Effect of Affordability of Live Streaming Shopping Information Technology On Consumer Buying Interest - Tauchid, Rahma Fatiha; Ghea Sekar Palupi (Journal of Education Technology and Information System, 2026)
The latest innovation from business information technology that is popular until now is live streaming shopping, a new marketing concept that combines live streaming with shopping activities. The birth of this new marketing trend or concept has been adopted by many large platforms, one of which is Shopee. Some business people utilise this platform to promote various products with a more general target. Although it offers many advantages, there are still problems in the use of information technology in this feature. This research was conducted with the aim of analyzing things that can influence consumer buying interest in the shopee live feature when viewed from the IT Affordance aspect with the Structural Equation Modelling-Partial Least Square (SEM-PLS) approach. This study indicates that IT Affordance through live streaming engagement has a positive effect on user purchase intention on the shopee live feature. These findings aim to identify the influence of IT Affordance and provide practical benefits for e-commerce users in order to design technology-based marketing strategies to increase engagement and support product purchase decisions.